Influences of Quinoid Structures on Stability and Photovoltaic Performance of Nonfullerene Acceptors. Issue 10 (9th August 2020) - Lv, Ruizhi; Geng, Shizhe; Li, Shuixing; Wu, Fei; Li, Yaokai; Andersen, Thomas Rieks; Li, Yuhao; Lu, Xinhui; Shi, Minmin; Chen, Hongzheng
Abstract : Although benzoazole‐fused rings with strong quinoid character have successfully been used to construct high‐performance small‐molecule non‐fullerene acceptors (NFAs), studies into how these units influence the stabilities of NFAs and their corresponding device performances are few to date. To address it, four new NFAs, SSTI, SNTI, NTI and NTTI, which adopt BBT, TBZ, and BTAZ as the cores, respectively, are designed and investigated. It is found that SSTI and SNTI based on BBT and TBZ cores with stronger quinoid resonance effects show features of more red‐shifted absorptions and deeper energy levels, but worse thermal and light stabilities than NTI and NTTI with a BTAZ core, especially in solutions and/or films blended with polymer donors. Through matrix‐assisted laser desorption ionization time of flight mass spectrometry analysis of the degradation products, it is disclosed that the CC double bond cleavage would be accelerated by stronger quinoid effects. Therefore, NTI and NTTI with relatively weaker quinoid characteristics show improved photovoltaic properties. Especially, NTTI based devices yield a good efficiency of 8.61% as the side chains on sp3‐hybrid C atoms can prevent the formation of large aggregates. These findings can provide invaluable knowledge for the molecular design of NFAs with both high‐efficiency and high‐stability Abstract : Four new acceptors with different quinoid effects are prepared for solution‐processed organic solar cells. The excessive azole rings and weak steric repulsion are found to obviously decrease the stabilities, and the stabilities are remarkably reduced in solution state. Finally, by reducing the quinoid effects, the power conversion efficiencies of the devices are greatly boosted from 0.05% to 8.61%.